2019
DOI: 10.1039/c8an01494a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Raman spectroscopy effectiveness in determining the early changes in human enamel caused by artificial caries

Abstract: Raman maps indicate the changes in enamel affected by the early demineralization process with the use of new parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Since the condition of human teeth is determined by changes occurring in the phase composition of the tissue at the micro and nano level, the use of spectroscopic methods of molecular identification is the most promising and sensitive tool to precisely assess such changes in the dental enamel [24][25][26] . Raman spectroscopy is most often used for diagnostics of dental diseases as a non-destructive method of analysis, which allows to obtain direct data regarding the local atomic structure, chemical and molecular composition of biological objects 18,20,24,[27][28][29] . Also, the hard tissue of a human tooth can be investigated by infrared spectroscopy methods [30][31][32][33][34] , which due to minimal external influences, has not been modified by the method 35 .…”
Section: This Study Is Aimed At Investigating the Features Of Mineralmentioning
confidence: 99%
“…Since the condition of human teeth is determined by changes occurring in the phase composition of the tissue at the micro and nano level, the use of spectroscopic methods of molecular identification is the most promising and sensitive tool to precisely assess such changes in the dental enamel [24][25][26] . Raman spectroscopy is most often used for diagnostics of dental diseases as a non-destructive method of analysis, which allows to obtain direct data regarding the local atomic structure, chemical and molecular composition of biological objects 18,20,24,[27][28][29] . Also, the hard tissue of a human tooth can be investigated by infrared spectroscopy methods [30][31][32][33][34] , which due to minimal external influences, has not been modified by the method 35 .…”
Section: This Study Is Aimed At Investigating the Features Of Mineralmentioning
confidence: 99%
“…Previous studies have also used Raman spectroscopy to determine the mineral composition of dental hard tissues 14,15,17,26 . Raman composition maps (using a step size of 50 µm) have been used previously to identify enamel demineralization caused by artificial caries using intensity and FWHM of V 1 PO 4 3band, depolarization ratio, and polarization anisotropy 26 . Where, based on the chemical analysis, they concluded that demineralized enamel tissues have a disordered structure at very early stages.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, Raman spectroscopy has been used in the early detection and characterization of dental caries, analysis of fluorosis-affected teeth and chemical profiling of adhesive/caries-affected dentin interface, for example. [11][12][13][14][15] Raman spectroscopy have major advantages over other optical spectroscopy techniques, such as IR spectro-scopy, when considering biological specimens. These include minimal sample preparation and the weak Raman interference with water.…”
Section: Introductionmentioning
confidence: 99%
“…Strong fluorescence background causes also problems in Raman analyses of teeth, especially when caries-affected teeth are measured. 12,[20][21][22] A commonly used method to suppress the problematic fluorescence background both generally and specifically in Raman analyses of teeth is to use longer excitation wavelengths in the near-infrared region of the electromagnetic spectrum. 12,20,23 The disadvantage of this technique is that also the already faint Raman signal weakens to the fourth power of the wavelength and thus, the SNR tends to stay low, especially when highly fluorescent samples, such as caries-affected teeth, are measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation